ANALISIS SINTAKSIS FUNGSI KALIMAT IMPERATIF BAHASA BATAK DALAM FILM “NGERI-NGERI SEDAP KARYA BENE DION RAJAGUKGUK SEBAGAI ALTERNATIF BAHAN AJAR - Putri Khoirunnisa; Dindin M.Z.M; Musaddad Abdul Aziz (STKIP Subang, 2023)
This research was conducted to provide solutions to the problems experienced by teachers. One of them is in determining the right teaching materials to be used by students so that they are interesting and not boring. In addition, students who have difficulty in writing review texts are also a problem. This research is expected to be able to provide solutions to problems in determining teaching materials and in accordance with the study of review texts at MTs Matlaul Anwar Dahu Pandeglang. The purpose of this study was to analyze the syntax of the imperative sentence functions of the Batak language in the film